Chemical Composition, Larvicidal Activity, and Enzyme Inhibition of the Essential Oil of Lippia grata Schauer from the Caatinga Biome against Dengue Vectors - Stênio Freitas Felix; Alzeir Machado Rodrigues; Ana Livya Moreira Rodrigues; José Claudio Carneiro de Freitas; Daniela Ribeiro Alves; Alice Araújo da Silva; Dayanne Lima dos Santos; Kethelly Rayne Lima de Oliveira; Renato Almeida Montes; Marcus Vinicius Ferreira da Silva; Francisco Flávio da Silva Lopes; Selene Maia de Morais (MDPI AG, 2021)
Insect resistance and environmental pollution are among the drawbacks of continuous use of synthetic insecticides against the vectors of dengue, Aedesaegypti and Aedes albopictus. The objective of this study was to analyze the composition of the essential oil of Lippia grata Schauer collected from plants, in three periods of the year, to compare the larvicidal activity and enzymatic inhibition of the dengue vectors. The oilsanalyzed by gas chromatography coupled to mass spectrometry (GC-MS), presented thymol and 1,8-cineole, as the main constituents, in all three periods. This composition was different from that found in previous studies of the species from different places, thus, suggesting a new chemotype of Lippia grata. Larvicidal tests were performed at concentrations of 100, 75, 50, 25, and 12.5 μg.mL−1 and the essential oil from the rainy season showed the best results, with LC50 of 22.79 μg.mL−1 and 35.36 μg.mL−1 against Ae. aegypti and Ae. albopictus, respectively; this result was better than other reports. In the rainy period, however, there was a greater variety of components, which led to a better larvicidal effect, possibly due to synergistic action with minor constituents. Total proteins, amylases, and acetylcholinesterase of both species were inhibited by the oils.